Rectangular microstrip 4x3 patch array antenna at 2.4 GHz for WLAN application: article / Siti Thaqifah Md Zin - Md Zin, Siti Thaqifah (2016)
In this paper, microstrip patch antennas are presented. Based on the array concept the array antennas were designed at 2.4GHz and investigated in terms of return loss, size and gain. It was found that 4x3 patch array antenna gave best performance compared to the other patch antennas. The 4x3 patch array antennas was then fabricated and measured using RO4350 microstrip substrate. Good agreement between simulation and measurement was observed for the 4x3 patch array antenna.